Rheological Behavior of Drilling Muds and Developing a Rheological Model - Kamisli, Fethi (Taylor & Francis Inc, 2025)
In our research described here, a rheological model was proposed to be used to determine the rheological behavior of drilling mud, which is one of the most important factors in determining a suitable mud used in drilling. The parameters of the rheological model were determined by a curve fitting method using more than 95 experimental data pairs available in the literature for seven different viscoelastic drilling muds. The relationship between shear stress and shear rate obtained from the proposed model was compared with the relationships obtained from the Herschel-Bulkley, Power-law, and Bingham plastic models. The data obtained from the proposed model was also compared with the experimental data existing in the related literature. The average percentage differences between the experimental data and the data obtained from the proposed model for the drilling fluids were 5.16, 0.623, and 8.8, respectively, which were considerably lower than the average differences between the experimental data and the data acquired from the three mentioned models. The Power-law model outperformed our proposed model for only three drilling muds. As a result, we suggest that the rheological model proposed here can be easily used to determine the rheological properties of some kinds of drilling muds. In addition to deriving the rheological model for drilling muds, a comprehensive literature review on the subject was conducted.
Keywords: Drilling muds; model; rheology; viscoelasticity